Cross-sectional association between the isocaloric replacement of carbohydrates with protein and fat in relation to fat compartments distribution and hepatic lipid content in recent-onset type 1 and type 2 diabetes - Alexander Lang; Edyta Schaefer; Yuliya Kupriyanova; Janina Goletzke; Katharina S. Weber; Anette E. Buyken; Sabine Kahl; Oana-Patricia Zaharia; Christian Herder; Vera B. Schrauwen-Hinderling; Oliver Kuss; Robert Wagner; et al. (Nutrition Journal)
Abstract Background Diets restricted in carbohydrates may be beneficial for diabetes management. However, without reducing energy intake, carbohydrate restriction results in increased protein and fat intake. Understanding how this macronutrient substitution is associated with adipose tissue distribution is important to prevent diabetes progression. Therefore, the aim was to investigate the isocaloric substitution of carbohydrates with fat and protein in relation to subcutaneous (SAT) and visceral adipose tissue (VAT) and hepatic lipid (HL) content in individuals with recent-onset type 1 (T1D) and type 2 diabetes (T2D), accounting for macronutrient quality. Methods This cross-sectional analysis includes participants with T1D (n = 137) and T2D (n = 170) from the German Diabetes Study (GDS). Dietary macronutrient intake was derived from dietary information assessed with a validated food frequency questionnaire. SAT and VAT were measured with magnetic resonance (MR) imaging, while HL content with 1H MR spectroscopy. Isocaloric substitution analyses based on multivariable linear regression models were conducted to examine the replacement of total and higher glycemic index (GI) carbohydrates in energy percent (En%) with total fat, monounsaturated (MUFA), polyunsaturated (PUFA), and saturated fatty acids (SFA), and protein in regard to SAT, VAT and HL content. Results In individuals with T1D, substituting carbohydrates with total fat was not associated with SAT, while substituting carbohydrates with protein demonstrated higher SAT [β (95% CI) per 5 En%: 3100 cm3 (25, 6200)]. In individuals with T2D, replacing carbohydrates with total fat or protein showed no association with SAT and VAT. However, substituting carbohydrates with PUFA was associated with lower VAT [-970 cm3 (-1900, -40)] and HL content [-3.3% (-6.9, 0.4)], while replacing carbohydrates with SFA was associated with higher HL content [2.4% (-0.6, 5.4)]. Substituting carbohydrates with protein was associated with lower HL content in individuals with T2D [-2.4% (-4.9, 0.0)], mainly driven by plant-based protein. There were no substantial differences between the replacement of total and higher GI carbohydrates. Conclusions The quality of substituted nutrients may play an important role for adipose tissue and HL accumulation in individuals with T2D. Particularly, integrating PUFAs and plant-based proteins into the diet seems beneficial for VAT and HL content.